Paciente pediátrico de 5 años con asma bronquial. - Jiménez Salazar, Wilson Isidro (2021)
Bronchial asthma is a respiratory disease that affects the airways (bronchi) most often in people, where the bronchial tubes become inflamed, blocking the passage of atmospheric air into the lungs. Bronchial asthma is more recurrent in childhood and affects more than 10% of the world population. These episodes are caused by allergic reactions in the airways that cause narrowing of the bronchial walls, interfering with the respiratory process. Asthma episodes or attacks can be serious, they can even interrupt the infant's daily activities and thus have a significant impact on quality of life and can become fatal without treatment.